Pengaruh Likuiditas dan Leverage Terhadap Agresivitas Pajak (Study kasus Perusahaan Manufaktur pada Sub Sektor Food and Beverage yang Terdaftar di BEI Tahun 2016-2019) - Nurizah hurrohma; Meta Ardiana (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2021)
Tax aggressivenes is a action taken by a company to reduce taxable income by avoiding tax. The pupose of this study was to examne and analyze the effect of liquidity and leverage on tax aggressiviness. This research was conducted on the Indinesia Stok Exchange by selecting the population in the foood and beverage sub-sector for the 2016-20019 period and using a purposive sampling method. The type oof research used is quantitative research. The results of this study indicate thaat the result of the first test show that the liquidity variable does not have a significant effect on tax aggressiveness. The results of testing the secound hypothesis show that the leverage variable is not proven to have a significant effect on corporate tax aggressiveness. Keywords: Liquidity, Leverage, Tax Aggressivenes.